Pengaruh Berkumur Rebusan Daun Sirih Merah (Piper crocatum Ruiz & Pav.) Terhadap Status Kebersihan Gigi dan Mulut serta Derajat Keasaman Saliva Pada Anak Usia 10 – 11 Tahun - Farah Fadhilah Putri; Emma Kamelia; Tritania Ambarwati; Anang Anang; Lina Rismayani (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2020)
Plaque buildup on the tooth surface and a decrease in salivary pH can be a risk of dental caries. Children aged 10-11 years are an age that is prone to dental and oral health problems such as dental caries. The percentage of children who have caries at the age of 10-11 years is 82%. Red betel leaf is known to contain antibacterial compounds that can be used as natural ingredients in making mouthwash to inhibit plaque formation and increase salivary pH. The research objective: to determine the effect of red betel leaf decoction (Piper crocatum Ruiz Pav.) on oral hygiene and the degree of acidity of saliva in children aged 10-11 years. Research methods: using a quasi-experimental design with one group pre-test and post-test designs. Sampling by purposive sampling as many as 20 people. The research measuring instrument used the PHP index and saliva pH. Data analysis used the Wilcoxon test. The results: after gargling red betel leaf stew, the average oral hygiene status increased from 2.90 to 1.98 and the degree of saliva acidity increased from 6.65 to 7.7, the Wilcoxon test results obtained p-value = 0.000 (0.05). Conclusion: there is an effect of gargling red betel leaf decoction on oral hygiene status and the degree of acidity of saliva in children aged 10-11 years.